Towards a Model of a Scalable Middleware Architecture Based on Cloud Computing, Application Reliable Integration and E-Learning Platforms in Academic Information Systems - Hassani, Abdellah Lalaoui; Mansouri, Khalifa (Transactions on Engineering and Computing Sciences, 2017)
Throughout the present article , we will examine, on the one hand, systems integration approaches of e-Learning applications in university’s information systems. On the other hand, we will establish a study about the integration of applications between the internal information systems and the Cloud. Then between the applications on the private cloud and the public cloud.